Peningkatan Kompetensi Supervisi Kepala Sekolah Melalui Pembinaan Pengawas secara Rutin bagi Kepala Sekolah Dasar se-Wilayah Gugus Sekolah Ronggolawe Kecamatan Cepu Kabupaten Blora Semester I Tahun 2015/2016 - Sudarbi Sudarbi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The purpose of this research is to improve the Head Master’s supervision competencies through routin coaching on Ronggolawe Group of Region II, Sub-District of Cepu, District of Blora, First Semester of 2015//2016 Year Academic. This research is an action research with 10 subjects. This research takes on First Semester of 2015//2016 Year Academic. The tools of collecting data are sheet of assessment and sheet of observation. This research is consist of two cycles. The result of this research is the improvement of the elementary head master’s supervision competencies. On the First Cycle, supervision competencies of the subjects are the average of competencies on arranging the Annual Program as 69,5, the average of competencies on arranging the Semester Program as 65 and the average of supervision competencies as 75,289. On the Second Cycle, supervision competencies of the subjects are the average of competencies on arranging the Annual Program as 82 the average of competencies on arranging the Semester Program as 80,5 and the average of supervision competencies as 90,28.